BCR-ABL Independent Mechanisms of Resistance in Chronic Myeloid Leukemia - Loscocco, Federica; Visani, Giuseppe; Galimberti, Sara; Curti, Antonio; Isidori, Alessandro (Frontiers in Oncology, 2019)
Not all chronic myeloid leukemia (CML) patients are cured with tyrosine kinase inhibitors (TKIs), and a proportion of them develop resistance. Recently, continuous BCR-ABL gene expression has been found in resistant cells with undetectable BCR-ABL protein expression, indicating that resistance may occur through kinase independent mechanisms, mainly due to the persistence of leukemia stem cells (LSCs). LSCs reside in the bone marrow niche in a quiescent state and are characterized by a high heterogeneity in genetic, epigenetic and transcriptional mechanisms. New approaches based on single cell genomics have offered the opportunity to identify distinct subpopulations of LSCs at diagnosis and during treatment. In the one hand, TKIs are not able to efficiently kill CML-LSCs, but they may be responsible for the modification of some LSCs characteristics, thus contributing to heterogeneity within the tumor. In the other hand, the bone marrow niche is responsible for the interactions between surrounding stromal cells and LSCs, resulting in the generation of specific signals which could favor LSCs cell cycle arrest and allow them to persist during treatment with TKIs. Additionally, LSCs may themselves alter the niche by expressing various costimulatory molecules and secreting suppressive cytokines, able to target metabolic pathways, create an anti-apoptotic environment and alter immune system functions. Accordingly, the production of an immunosuppressant milieu may facilitate tumor escape from immune surveillance and induce chemo-resistance. In this review we will focus on BCR-ABL-independent mechanisms, analyzing especially those with a potential clinical impact in the management of CML patients.